2000
DOI: 10.1073/pnas.200348197
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide DNA sequence variation in a 10-kilobase noncoding region on human chromosome 22

Abstract: Human DNA sequence variation data are useful for studying the origin, evolution, and demographic history of modern humans and the mechanisms of maintenance of genetic variability in human populations, and for detecting linkage association of disease. Here, we report worldwide variation data from a Ϸ10-kilobase noncoding autosomal region. We identified 75 variant sites in 64 humans (128 sequences) and 463 variant sites among the human, chimpanzee, and orangutan sequences. Statistical tests suggested that the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
83
3
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(101 citation statements)
references
References 25 publications
13
83
3
1
Order By: Relevance
“…To explain this and given the values of c, we can only assume that c, Ne, or both are higher in the mouse genome. Ne was estimated to be approximately 10,000 in the human lineage (Takahata et al 1995;Zhao et al 2000;Yu et al 2003;Keightley et al 2005) and between 450,000 and 810,000 in the mouse lineage (Keightley et al 2005). These values are in agreement with our results.…”
Section: The Effect Of Bgcsupporting
confidence: 92%
“…To explain this and given the values of c, we can only assume that c, Ne, or both are higher in the mouse genome. Ne was estimated to be approximately 10,000 in the human lineage (Takahata et al 1995;Zhao et al 2000;Yu et al 2003;Keightley et al 2005) and between 450,000 and 810,000 in the mouse lineage (Keightley et al 2005). These values are in agreement with our results.…”
Section: The Effect Of Bgcsupporting
confidence: 92%
“…For instance, we find that the analyses of pseudogenes (Li and Tanimura 1987;Nachman and Crowell 2000;Martinez-Arias et al 2001) and introns (Bergstrom et al 1999;Chen et al 2001) have produced much lower estimates of evolutionary divergence than those observed in synonymous sites in protein coding genes (Li and Tanimura 1987;Wolfe et al 1989;Easteal 1991;Keightley and Eyre-Walker 2000;Duret et al 2002;Kumar and Subramanian 2002). Also, intergenic DNA (excluding regulatory sites), which is expected to mutate at a rate similar to that for the coding DNA, also consistently shows much smaller evolutionary divergences than those obtained from coding sequences (Bohossian et al 2000;Zhao et al 2000;Chen et al 2001;Mathews et al 2001;Yu et al 2001). This observation is not a random chance occurrence due to paucity of data, because these studies have involved direct comparisons of long intergenic regions (Bohossian et al 2000;Zhao et al 2000;Chen et al 2001) and relatively large numbers of coding genes (Wolfe et al 1989;Keightley and Eyre-Walker 2000;Duret et al 2002;Kumar and Subramanian 2002).…”
mentioning
confidence: 72%
“…Also, intergenic DNA (excluding regulatory sites), which is expected to mutate at a rate similar to that for the coding DNA, also consistently shows much smaller evolutionary divergences than those obtained from coding sequences (Bohossian et al 2000;Zhao et al 2000;Chen et al 2001;Mathews et al 2001;Yu et al 2001). This observation is not a random chance occurrence due to paucity of data, because these studies have involved direct comparisons of long intergenic regions (Bohossian et al 2000;Zhao et al 2000;Chen et al 2001) and relatively large numbers of coding genes (Wolfe et al 1989;Keightley and Eyre-Walker 2000;Duret et al 2002;Kumar and Subramanian 2002). This difference between coding and noncoding regions in interspecies comparisons is also seen in within-species analysis of single nucleotide polymorphisms (SNPs) that show higher nucleotide diversity in the synonymous sites of exons compared to the noncoding DNA (Moriyama and Powell 1996;Cargill et al 1999;Halushka et al 1999;Zwick et al 2000).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Comparison of the ratio of polymorphisms to fixed differences at IL13 with a 10 kb noncoding region of chromosome 22 39 and intron 44 of the DMD gene 40 (both assumed to be evolving under neutrality), using an HKA test, showed no significant difference (P40.13), indicating that the IL13 gene does not show an excess or depletion of variation compared to these other loci. Additionally, sliding window analysis of differences in the ratio of polymorphism/fixed differences across the gene using several statistics (K R , D KS and G mean 31 ) indicates no evidence for significant heterogeneity in the pattern of genetic diversity across the IL13 Table 4 Continued Position 2043 (bold characters) is the only nonsynonymous substitution (Arg130Gln).…”
Section: Tests Of Neutralitymentioning
confidence: 99%